Effect of Noise on General Health Status of Electrical Generator Workers in Iraq - Mohammed Fakhri Azeez; Fatima Wanas Khudair2; Ali A. Al-Fahham (Indian Journal of Forensic Medicine & Toxicology, 2021)
Electrical generators in Iraq have been a series problem regarding occupational and environmental pollution.The current study aimed to determine the level of general health status among generator workers in AlDiwaniyah City Iraq, and its correlation with noise and demographic data . A descriptive cross-sectionaldesign was conducted in the current study . It was carried out at the private electrical generators inA-Diwaniyah City from the period between the 15th of October 2020 until the 15th of March 2021 . Apurposive study of 150 generator workers has been selected .General health was determined by GeneralHealth questionnaire (GHQ-28) which is comprised of 28 items, and include four aspects : somatic, social, depression and anxiety . Noise intensity level was measured by sound level meter (SLM) . The results ofthe present study revealed that average level of noise intensity inside the workers’ room was (78.12 db) ;while it was (104.14 db) near the generator . The results also showed that the assessment of most domain(social, depression, and anxiety) was moderate, except for somatic domain which it was good . There was asignificant negative correlation between noise and depression and anxiety . It has been concluded that : Mostof the generator workers showed a moderate level of general health status ; Most of the generators workershad moderate level for anxiety, depression and social aspects ; Noise intensities inside the generator roomsexceeds the upper limits accepted for human health .